ANALISIS KUAT TARIK BELAH TERHADAP PEMANFAATAN LIMBAH STRAPPING BAND SEBAGAI SUBSTITUSI PASIR PADA BETON NORMAL - Dr. Akhmad Suryadi, BS., MT (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2019)
The advancement era, the use of strapping band in the process of shipping goods was increases because of the more practical needs and stronger straps make the waste from strapping band was increases. With a large amount of waste by shredding it into smaller sizes it can be used as a substitute for fine aggregate in concrete mixture with synthetic fiber reinforced concrete concept at the Laboratory of Civil Engineering Politeknik Negeri Malang. The objectives of this research were to analyze the characteristics of concrete with the substitution of strapping band waste against fine aggregate in compressive strength and split tensile strength test. The research method including: aggregate test and strapping band test, the mix design of concrete mixture was using the reference SNI 03-2834-2000. The experiments sample for each variation of 0%, 5%, and 8% were performed with 24 cylinder specimens for compressive strength and 6 cylinder specimens for split tensile strength. The compressive strength on 28 days with 0%, 5%, and 8% variation resulted in 27.67 kg/cm2; 26.82 kg/cm2; 17.83 kg/cm2. The split tensile strength on 28 days with 0% 5%, and 8% variation resulted in 2.42 kg/cm2; 1.90 kg/cm2; 1.51 kg/cm2. The average weight of cylinder specimens with 0%, 5%, and 8% variation resulted in 12.62 kg; 12.04 kg; 11.61 kg. Substitution of strapping band waste decreases compressive strength, split tensile strength and average weight concrete. Key words : Strapping band waste, compressive strength, split tensile strength